Erratum: Genetic Linkage Maps of the Guppy (Poecilia reticulata): Assignment of RAPD Markers to Multipoint Linkage Groups (Marine Biotechnology 5;3 (279-293)) - Khoo, G. (2014)
10.1007/s10126-003-0030-x